Education on the Application of Red Rose Aromatherapy for Pain Reduction in the First Stage of Labor - Sitorus, Riris; S, Grace Erlyn Damayanti; Br Barus, Eva Solina; Astari, Resha (JURNAL PENGMAS KESTRA (JPK), 2025)
Labor is a critical moment filled with anticipation, emotion, and physiological change for pregnant women. Pain during the first stage of labor is a natural process but often leads to physical discomfort and psychological distress, potentially prolonging labor and increasing complication risks. This community service program (PkM) was designed as an educational seminar aimed at promoting red rose-based aromatherapy as a non-pharmacological approach to alleviate labor pain in the first stage. The seminar involved 30 pregnant women as active participants and was conducted at Nining Pelawati Clinic. Educational content included an introduction to aromatherapy, the therapeutic benefits of red rose essential oil, its sensory mechanisms through the olfactory system, and the correct usage procedures according to standardized operational protocols. Participants’ knowledge was assessed using structured pre-test and post-test questionnaires. The results revealed a notable increase in participants’ understanding, with average scores rising from 55.2 (pre-test) to 88.1 (post-test), indicating a 59.6% improvement. The highest gain (80%) was observed in understanding standard procedures of aromatherapy application. These findings demonstrate that interactive, participatory education combined with supportive media such as leaflets and instructional videos is highly effective in enhancing knowledge. This program is expected to support pregnant women in preparing for childbirth with greater confidence, reduced anxiety, and improved coping mechanisms through natural pain management techniques.